2014
DOI: 10.1080/10410236.2014.895282
|View full text |Cite
|
Sign up to set email alerts
|

Do the Ends Justify the Means? A Test of Alternatives to the FDA Proposed Cigarette Warning Labels

Abstract: Three studies provide empirical, social scientific tests of alternatives to the originally proposed U.S. Food and Drug Administration (FDA) cigarette package warning labels on health risk beliefs, perceived fear, and effectiveness. Our research addresses questions at the root of the legal disputes surrounding FDA regulation of cigarette package warning labels. Specifically, we describe results from three studies that investigate the mediating role of health beliefs and perceived fear in shaping message effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…The number of images viewed and the amount of time they remained on-screen were selected to be consistent with prior literature on the FDA-proposed graphic warning labels. 54 Following the presentation of the stimuli, participants completed dependent measures. They were debriefed.…”
Section: Methodsmentioning
confidence: 99%
“…The number of images viewed and the amount of time they remained on-screen were selected to be consistent with prior literature on the FDA-proposed graphic warning labels. 54 Following the presentation of the stimuli, participants completed dependent measures. They were debriefed.…”
Section: Methodsmentioning
confidence: 99%
“…While this might be a challenge given legal difficulties in implementing pictorial warnings for tobacco cigarettes, the previous rulings against graphic cigarette warnings related to the specific images used and not the government’s use of graphic warnings in principle [ 22 ]. As such, potential pictorials for e-cigarette warnings could be planned appropriately, perhaps making use of symbols associated with addiction (e.g., chains, brain) or caution (e.g., yellow triangle) [ 23 ] rather than graphic health effects or negative emotions (e.g., person crying) proposed for tobacco cigarettes that might be criticized as “overly emotional” or “more extensive than necessary” [ 19 , 20 ]. Alternatively, if young people are the primary audience for e-cigarette warnings, pictorials could potentially depict images of young people to both attract attention and communicate that the message is aimed at them (unless formative research finds this unintentionally increases young peoples’ product interest).…”
Section: Discussionmentioning
confidence: 99%
“…Already two tobacco companies have proposed modifying warnings for smokeless tobacco products to indicate they present less risk than cigarettes, though these have not been approved by the FDA [ 17 , 18 ]. In addition, the legal challenges the FDA has faced with regulation over e-cigarettes in general and in trying to implement new high impact graphic warning labels to tobacco cigarettes (criticized as being overly emotional and more extensive than necessary) [ 19 , 20 ] also suggests the need for careful consideration of not only what might be ideal in terms of developing effective e-cigarette warnings, but also legally plausible.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the evidence from studies based on cigarette health warnings indicates that cognitive and affective mediators underlie the effectiveness of health warnings. These studies have consistently found that compared to text-only warnings, warnings with graphic images elicited greater fear arousal, which in turn increased intentions to quit (Kees, Burton, Andrews, & Kozup, 2010), perceived risk (Emery et al, 2014), as well as perceived and actual effectiveness (Byrne, Katz, Mathios, & Niederdeppe, 2015). …”
Section: Introductionmentioning
confidence: 95%